2021
DOI: 10.1080/07853890.2021.1894009
|View full text |Cite
|
Sign up to set email alerts
|

Molecular biomarkers associated with respiratory insufficiency in amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a devastating and fatal neurodegenerative disorder.Death typically occurs within 3–5 years after disease onset. The main cause of death in ALS is respiratory failure (RF). No effective treatment is available and no molecular biomarker related to respiratory outcome and to early ventilatory dysfunction was described so far. The club-cell protein (CC-16) is a biomarker associated with respiratory distress and lung inflammation. The aim of this work is to test if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In addition, emerging evidence suggests that abnormalities in erythrocyte morphology in patients with ALS may contribute to the risk of aggregation and thrombosis. 10 The strengths of this study include the use of a large sample of patients with ALS identified from a US claims database including over 100 million individuals. This real-world sample of patients with ALS from across diverse medical settings in the United States likely represents a more representative sample of patients with ALS than previous smaller and single-institution-based studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, emerging evidence suggests that abnormalities in erythrocyte morphology in patients with ALS may contribute to the risk of aggregation and thrombosis. 10 The strengths of this study include the use of a large sample of patients with ALS identified from a US claims database including over 100 million individuals. This real-world sample of patients with ALS from across diverse medical settings in the United States likely represents a more representative sample of patients with ALS than previous smaller and single-institution-based studies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, emerging evidence suggests that abnormalities in erythrocyte morphology in patients with ALS may contribute to the risk of aggregation and thrombosis. 10 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, erythrocytes have abnormal biophysical properties and morphology in patients with ALS, probably favoring aggregation and thrombotic events. 10 Although we need more information about the significance of these red cell changes described in ALS, the potential influence on the risk of VTE should be explored.…”
mentioning
confidence: 99%